Discovery of Dome‐Shaped Superconducting Phase and Anisotropic Transport in a van der Waals Layered Candidate NbIrTe4 under Pressure. Issue 24 (1st November 2021) - Jin, Meiling; Yu, Peng; Fan, Changzeng; Li, Qiang; Kong, Panlong; Shen, Zhiwei; Qin, Xiaomei; Chi, Zhenhua; Jin, Changqing; Liu, Guangtong; Zhong, Guyue; Xu, Gang; et al.
Abstract: The unique electronic structure and crystal structure driven by external pressure in transition metal tellurides (TMTs) can host unconventional quantum states. Here, the discovery of pressure‐induced phase transition at ≈2 GPa, and dome‐shaped superconducting phase emerged in van der Waals layered NbIrTe4 is reported. The highest critical temperature ( T c ) is ≈5.8 K at pressure of ≈16 GPa, where the interlayered Te–Te covalent bonds form simultaneously derived from the synchrotron diffraction data, indicating the hosting structure of superconducting evolved from low‐pressure two‐dimensional (2D) phase to three‐dimensional (3D) structure with pressure higher than 30 GPa. Strikingly, the authors have found an anisotropic transport in the vicinity of the superconducting state, suggesting the emergence of a "stripe"‐like phase. The dome‐shaped superconducting phase and anisotropic transport are possibly due to the spatial modulation of interlayer Josephson coupling . Abstract : The correlation of novel electrical properties and structural evolutions in van der Waals layered material is revealed by performing special high‐pressure measurements. A superconducting model is proposed to explain the emergence of "stripe"‐like phases and the evolution of critical temperature. Spatial modulation of interlayer Josephson coupling furthers the understanding of the complex relationships between structure, anisotropy, and superconductivity.